SAPI DALAM SOSIAL-BUDAYA MASYARAKAT MADURA ABAD 19-20 - Mohammad Refi Omar Ar Razy; Dade Mahzuni (Prodi Ilmu Sejarah, Jurusan Sejarah, Seni dan Arkeologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, bekerja sama dengan Masyarakat Sejarawan Indonesia, Jambi, 2022)
This study attempts to analyze the conservation of cattle in Madura and its relationship with social, cultural and economic studies. Cows are very synonymous with the Madura people’s. In the cultural context, the cows has become a custom for the Madura people’s. It is proven by the existence of an event that involves cows in it, namely the Karapan Sapi festival. For the Madura people’s, Karapan Sapi is not only an ordinary festival activity, but in it there are traditional values and also noble values that also involve the dignity of the Madurese. Cows, which are a custom for the Madura people’s, must be taken care of properly. In the social and economic context, the cows symbolizes the structure and class of the Madura people’s and also symbolizes self-esteem in everyday life. Its motto is